2001
DOI: 10.1111/j.1751-0813.2001.tb10713.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of high‐speed treadmill videoendoscopy for diagnosis of upper respiratory tract dysfunction in horses

Abstract: The results of this study are similar to reports from overseas and suggest high-speed treadmill videoendoscopy appears to be a useful technique to diagnose the cause of upper airway dysfunction in Australian horses referred specifically for poor performance associated with abnormal upper respiratory noise. However, a diagnosis will not be made in all horses undergoing this procedure. There were five horses with two or three abnormalities none of which were apparent at rest. This would suggest that in all horse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
75
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 8 publications
10
75
0
Order By: Relevance
“…These results are comparable with studies in similar populations overseas where dynamic obstruction was identified in 65% -77% of horses (Dart et al 2001;Davidson et al 2011;Desmaizieres et al 2009;Franklin, Naylor & Lane 2006;Witte et al 2011).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…These results are comparable with studies in similar populations overseas where dynamic obstruction was identified in 65% -77% of horses (Dart et al 2001;Davidson et al 2011;Desmaizieres et al 2009;Franklin, Naylor & Lane 2006;Witte et al 2011).…”
Section: Discussionsupporting
confidence: 87%
“…Multiple abnormalities were observed in 50% of the horses examined ( Figure 5 and Figure 6), which is similar to the findings of Tan, Dowling and Dart (2005) and Dart et al (2001), who reported that 49% and 73% of horses in their study populations, respectively, had multiple respiratory abnormalities in contrast to another study that identified a lower proportion (32%) of horses with multiple respiratory abnormalities (Lumsden et al 1995). The detection of multiple abnormalities may be influenced by the population examined, evaluator expertise and the type of exercise performed (e.g.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations